The potential of β-sitosterol to protect and to programme for protection against diet-induced metabolic derangements in sprague-dawley rats - Gumede, Nontobeko Myllet (My University, 2020)
The consumption of high-fructose diets contributes to the development of metabolic syndrome (MetS), non-alcoholic fatty liver disease (NAFLD), chronic kidney disease (CKD) in children and adults. Neonatal fructose intake programmes for metabolic derangements in later life. β sitosterol has been shown to have nutritional and health benefits. In two major experiments, I interrogated the potential protective effects of β-sitosterol against the development of high fructose diet-induced metabolic dysfunction, NAFLD and renal derangements. In the first experiment, I investigated the long-term daily intake of β-sitosterol against high-fructose diet induced metabolic derangements. Seventy 21-day old Sprague-Dawley rat pups (35 female ; 35 male) were, in an interventional study, randomly allocated to and administered treatments as follows: group I- standard rat chow (SRC) + plain drinking water (PW) + plain gelatine cube (PC); group II- SRC+ 20% w/v fructose solution (FS) as drinking fluid + PC; group III- SRC + FS + 100 mg/kg fenofibrate in gelatine cubes; group IV- SRC + FS + 20 mg/kg β-sitosterol in gelatine cube (Bst) and group V- SRC + PW + Bst. Following 12 weeks of feeding, the rats were fasted overnight, weighed, then euthanised and tissues collected for analyses. Surrogate biomarkers of liver and kidney function, cholesterol, insulin, triglyceride and adiponectin concentrations were determined from plasma. Dietary fructose caused (p < 0.05) visceral obesity, hypoadiponectinaemia, micro- and macro-vesicular hepatic steatosis, decreased glomerular density and increased kidney-injury molecule-1 (KIM-1) in growing female and male rats. Additionally it caused (p < 0.05) hypertriglyceridaemia in adult female rats only. β-sitosterol prevented the high-fructose diet-induced derangements except the increase in KIM-1. The second experiment evaluated the potential of neonatal orally administered β-sitosterol to programme for protection against high-fructose diet-induced metabolic derangements in adulthood. Seventy 4-day old Sprague-Dawley rat pups (34 female; 36 male) were acclimatised to handling for two days (PND 4-5) following which they were, in an interventional study, randomly allocated to one of the following treatment regimens: group I - DMSO + PW = gavaged daily with 10 mL/kg body mass 0.5% v/v dimethyl sulfoxide (DMSO) at pre-weaning + ad libitum access to plain drinking fluid at post-weaning; group II- FS + FS = gavaged daily with 10 mL/kg body mass 20% fructose solution (w/v) in 0.5% v/v DMSO at pre-weaning + ad libitum access to 20% fructose solution (w/v) as drinking fluid at post-weaning, group III- Bst + PW = gavaged daily with 20 mg/kg body mass β-sitosterol in 0.5% v/v DMSO at pre-weaning + ad libitum access to plain drinking fluid at post-weaning and, group IV- Bst + FS = gavaged daily vii with a bolus of 20 mg/kg β-sitosterol dissolved in 0.5% v/v DMSO plus 10 mL/kg body mass of 20% fructose solution (w/v) at pre-weaning + ad libitum access to 20% fructose solution (w/v) as drinking fluid at post-weaning. The pups were administered their respective treatments daily for 15 days (PND 6-21) and weaned on PND 21. On PND 125 the rats were fasted overnight and then euthanised on PND 126. Fasting blood glucose and triglyceride concentrations were determined and visceral fat pad collected for analyses of visceral obesity. Long-term high-fructose diet feeding caused NAFLD in adult female and male rats but caused visceral obesity in female rats only. The NAFLD progressed to non-alcoholic steatohepatitis (NASH) only in male rats. Neonatal β-sitosterol (Bst + FS) protected (p < 0.05 vs FS + FS) against the high-fructose diet-induced NAFLD in adult female and male rats but failed to prevent (p > 0.05 vs FS + FS) the fructose-induced visceral adiposity in female rats. In conclusion, findings from the first experiment suggest that chronic daily intake of β-sitosterol could potentially be exploited as a preventative intervention against high-fructose diet-induced visceral obesity, hypertriglyceridaemia, hypoadiponectinaemia, macro-vesicular hepatic steatosis and decrease in glomerular density. Findings from the second experiment demonstrated that neonatal orally administered β-sitosterol strategically targeting the developmentally plastic pre weaning phase may have long-term prophylactic effects against long-term high-fructose diet induced NAFLD
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Physiology, University of the Witwatersrand, Johannesburg, 2020